Innovativeness and Competitive Advantage among Small and Medium Enterprise Exporters: Evidence from Emerging Markets in South East Asia - Ismail, Md Daud; Alam, Syed Shah (UI Scholars Hub, 2019)
Research Aims: This study investigates the impact of innovativeness on competitive advantage along with the role of human capital and entrepreneurship orientation as drivers for innovation. Design/Methodology/Approach: The sample consists of small and medium sized manufacturers in Malaysia. A total of 193 firms participated. Data were collected via mail and drop-off survey and analysed using multiple regression analysis. Research Findings: The findings indicate that innovativeness significantly and positively influences competitive advantage. The effect of human capital and entrepreneurship orientation on innovativeness is also positive and significant. Theoretical Contribution/Originality: The findings of this study also have theoretical implications wherein the results lend support to the appropriate role of innovativeness in creating competitive advantage and its role in the human capital and entrepreneurship orientation towards innovativeness. Managerial Implications in the Southeast Asian context: The present study suggests that small and medium enterprises (SMEs) managers should focus on developing organisational value and capacity to encourage the creation of novel business solutions. These resources are entrepreneurship orientation (EO) and human capital. Successful export ventures, with a background of limited resources, can be achieved by employing incremental internationalisation frameworks. Research Limitations and Implications: This study bears several limitations. First, most of the samples are businesses owned by the Malay and may not be generalised to other ethnicities such as Chinese or SMEs in other emerging countries. Second, the competitive advantage is contingent on the external environment, and the results may vary when factoring in the effect of the external environment.